Orientation experiments with Mallard - Matthews, G V T (Wildfowl, 1961)
This is a short version of a paper entitled ’Nonsense orientation in Mallard and its relation to experiments on bird navigation,’ which appeared in Ibis 103a: 211-30 (1961). Mallard were caught and released at a distance from Slimbridge to check a report of migratory behavior, and to redistribute surplus stock over the countryside to everyone’s benefit.